A Systematic Review of Mobile Stroke Unit Among Acute Stroke Patients: Time Metrics, Adverse Events, Functional Result and Cost-Effectiveness - Chen, Jieyun; Lin, Xiaoying; Cai, Yali; Huang, Risheng; Yang, Songyu; Zhang, Gaofeng (Frontiers in Neurology, 2022)
Abstract Background: Mobile stroke unit (MSU) is deployed to shorten the duration of ischemic stroke recognition to thrombolysis treatment, thus reducing disability, mortality after an acute stroke attack, and related economic burden. Therefore, we conducted a comprehensive systematic review of the clinical trial and economic literature focusing on various outcomes of MSU compared with conventional emergency medical services (EMS). Methods: An electronic search was conducted in four databases (PubMed, OVID Medline, Embase, and the Cochrane Controlled Register of Trials) from 1990 to 2021. In these trials, patients with acute stroke were assigned to receive either MSU or EMS, with clinical and economic outcomes. First, we extracted interested data in the pooled population and conducted a subgroup analysis to examine related heterogeneity. We then implemented a descriptive analysis of economic outcomes. All analyses were performed with R 4.0.1 software. Results: A total of 22766 patients from 16 publications were included. 7682 (n=33.8%) were treated in the MSU and 15084 (n=66.2%) in the conventional EMS. Economic analysis were available in four studies, of which two were based on trial data and the others on model simulations. The pooled analysis of time metrics indicated a mean reduction of 32.64 minutes (95% confidence interval: 23.38-41.89, p<0.01) and 28.26 minutes (95% CI: 16.11-40.41, p<0.01) in the time-to-therapy and time-to-CT completion, respectively in the MSU. However, there was no significant difference on stroke-related neurological events (OR=0.94, 95% CI: 0.70-1.27, p=0.69) and in-hospital mortality (OR=1.11, 95% CI: 0.83-1.50, p=0.48) between the MSU and EMS. The proportion of patients with modified Ranking scale (mRS) of 0–2 at 90 days from onset was higher in the MSU than EMS (p<0.05). MSU displayed favorable benefit-cost ratios (2.16-6.85) and incremental cost-effectiveness ratio (31,911 /QALY and 38,731 per DALY) comparing to EMS in multiple economic publications. Total cost data based on 2014 USD showed that the MSU has the highest cost in Australia (1,410,708) and the lowest cost in the USA (783,463). Conclusion: A comprehensive analysis of current research suggests that MUS, compared with conventional EMS, has a better performance in terms of time metrics, safety, long-term medical benefits, and cost-effectiveness.